Pendekatan Kontekstual terhadap Al-Qur’an dan Sunnah dalam Menjawab Problematika Sosial di Indonesia - Destia Purwaningsih; Maulida Maulida; Nabela Nabela; Surya Sukti; Rafik Patrajaya (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study provides an in-depth analysis of the urgency of employing a contextual approach to the Qur’an and Sunnah as a hermeneutical framework for addressing the increasingly complex social problems in Indonesia. Based on the premise that divine revelation encompasses both textual and contextual dimensions, this research underscores the necessity of reinterpreting Islamic teachings by considering the sociocultural, economic, and intellectual transformations of modern society. Utilizing library research and extensive scholarly literature review, the study examines the contributions of the contextual approach in revitalizing maqāṣid al-sharī‘ah, advancing social exegesis, promoting productive zakat models, strengthening child protection policies, developing environmental jurisprudence, and enhancing social ijtihād during crisis situations such as the Covid-19 pandemic. The findings demonstrate that a contextual approach enables Islamic teachings to be articulated into more adaptive, inclusive, and progressive ethical principles without compromising their theological foundations. This approach also reinforces the integration of social sciences into Islamic studies, thereby producing legal formulations and public policies that promote public welfare, social justice, and ecological sustainability. Overall, the study concludes that the contextual approach is not merely a method of interpretation but a civilizational paradigm essential for shaping Islam’s relevance within Indonesia’s multicultural society. By fostering a dialogical encounter between scriptural texts and empirical realities, this approach preserves the vitality of Islamic teachings while ensuring their constructive and sustainable contribution to resolving national issues.